Marital and Inheritance Law from the Middle Ages to the Positive Law. From Scanderbeg Canon to Positive Law - Majlinda Belegu; Bashkim Rrahmani (Journal on European History of Law)
Family law is an important part of the civil law. Since the Roman Law this continues to be important part of this field. With the analysis of the paper the differences and similarities of norms from Scanderbeg, Lekë Dukagjini and Dibra Canon are underlined and emphasized. Paper covers and analysis the norms of historical law and customs through interpretation also positive norms of the countries where Albanian population lives. Engagement, marriage, the rights and duties of spouses during the marriage as regulated by the codexes through the history are analyzed as well as the disposal from sheria along with the rights and duties of spouses based on the positive law, for comparative reasons. Engagement is the first initiative before the marriage is concluded. Marriage was concluded after the engagement and it lasted until the death of spouses. The rights between spouses were always different where husband had more rights related to his wife. There were cases when he had the possibility to even kill his wife if the loyalty was not respected and also to divorce whenever he found it useful.